Insulin pump therapy in type 1 diabetes mellitus: education effectiveness and quality of life - Lyudmila Ibragimovna Ibragimova; Yury Ivanovich Filippov; Alexander Yur'evich Mayorov (Сахарный диабет)
Aim. To compare efficacy of special structured program for type 1 diabetes mellitus (DM) group education between users of an integratedreal-time (RT) continuous glucose monitoring (CGM)/continuous subcutaneous insulin infusion (CSII) systems and patientson CSII and self-monitoring of blood glucose (SMBG).Methods. This 4 months trial included 39 adults (18 male, age 27 [24,0;35,0] years) with type 1 DM (duration of diabetes 12[8,0;18,0] years). All subjects were randomized to study groups: 20 in the CSII/SMBG arm and 19 in the RT-CGM/CSII arm. Allparticipants were provided with special structured program for group education of diabetes patients on insulin pump therapy. Qualityof life (QoL) was assessed with questionnaire SF-36. Results. Both groups were not significantly different in HbA1c, BMI and QoL at baseline. After 4 months HbA1c was significantly lowerin both study groups without increase in rate of hypoglycemia. Improvements in QoL were observed in psychic health score in the CSII/SMBG arm and in physical health and psychic health scores in the RT-CGM/CSII arm. There was no significant difference in HbA1c,BMI and QoL between groups. Conclusion. Transfer to CSII during group training under special structured program for patients with type 1 DM significantly improvesglycemic control regardless of glucose monitoring method. Both RT-CGM+CSII and SMBG+CSII amend several aspects of QoL.Finally, transfer to CSII during group training considerably reduces total consumption of trainers time without loss of training quality.